Catalyst comprising zirconium oxide and gallium oxide components for producing C2 to C4 olefins

By using a mixed catalyst system combining gallium oxide and phase-pure zirconia in the catalyst, combined with SAPO-34 microporous catalyst, the problems of low efficiency and poor stability in the prior art are solved, and carbon with high yield and long life is achieved Conversion effect.

CN113748098BActive Publication Date: 2025-01-07DOW GLOBAL TECHNOLOGIES LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201980090309.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-16
Publication Date
2025-01-07
Estimated Expiration
2039-12-16

AI Technical Summary

Technical Problem

The catalysts used in the prior art for converting feed carbon into C2 to C4 olefins have low efficiency and poor stability, resulting in low carbon conversion and yield, and the catalyst is inactivated after a long operation time.

Method used

Using a mixed catalyst system including gallium oxide and phase-pure zirconium oxide and microporous catalyst components, the gallium and zirconium components are prepared by the primary wet impregnation method, combined with SAPO-34 microporous catalyst to ensure gallium and Zirconium is in close contact to improve catalytic activity and selectivity.

Benefits of technology

High and stable yields of C2 to C4 olefins and carbon conversion are achieved, extending the operating life of the catalyst and improving process stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003179911620000131
    Figure BDA0003179911620000131
  • Figure BDA0003179911620000132
    Figure BDA0003179911620000132
  • Figure BDA0003179911620000141
    Figure BDA0003179911620000141
Patent Text Reader

Abstract

A method for preparing C2 to C4 olefins comprises introducing a feed stream comprising hydrogen and a carbon-containing gas selected from carbon monoxide, carbon dioxide and mixtures thereof into a reaction zone of a reactor. The feed stream is converted into a product stream comprising C2 to C4 olefins in the presence of a mixed catalyst in the reaction zone. The mixed catalyst comprises a metal oxide catalyst component and a microporous catalyst component, the metal oxide catalyst component comprising gallium oxide and phase pure zirconium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 785,828, filed on December 28, 2018, the entire disclosure of which is hereby incorporated by reference. Technical Field

[0003] This specification generally relates to catalysts that effectively convert various carbonaceous streams into C2 to C4 olefins. Specifically, this specification relates to the preparation of mixed catalysts and the application of process methods to achieve high conversion of synthesis gas feed, thereby resulting in good carbon conversion and high yield of desired products. Synthesis gas includes hydrogen and a carbonaceous gas selected from the group consisting of carbon monoxide, carbon dioxide and mixtures thereof. Mixed catalysts generally include a combination of metal oxide components and microporous catalyst components that operate in sequence. Background Art

[0004] For many industrial applications, olefins are used, either as starting materials for the production of plastics, fuels and various downstream chemicals. Such olefins include C2 to C4 materials, such as ethylene, propylene and butylene (also commonly referred to as ethylene, propylene and butylene, respectively). A variety of methods have been developed for the production of these lower olefins, including petroleum cracking and various synthesis methods.

[0005] Synthesis methods for converting feed carbon to desired products, such as olefins, are known. Some of these synthesis methods begin with the use of mixed catalysts. Different types of catalysts, as well as different types of feed streams and ratios of feed stream components have also been studied. However, many of these synthesis methods have low carbon conversion rates, and a large portion of the feed carbon (1) is not converted and leaves the process in the same form as the feed carbon; (2) is converted to CO2; or (3) these synthesis methods have low stability over time, and the catalyst quickly loses its activity in converting carbon to the desired product. For example, many synthesis methods tend to have increased methane production over time - and therefore have reduced C2 to C4 olefin production.

[0006] Therefore, there is a need for processes and catalytic systems having high conversion of feed carbon to desired products, such as C2 to C4 olefins, and high operating stability of the catalyst. Summary of the invention

[0007] According to one embodiment, a method for preparing C2 to C4 olefins includes: introducing a feed stream including hydrogen and a carbon-containing gas into a reaction zone of a reactor, wherein the carbon-containing gas is selected from the group consisting of carbon monoxide, carbon dioxide and a mixture thereof; and converting the feed stream into a product stream including C2 to C4 olefins in the reaction zone in the presence of a mixed catalyst, wherein the mixed catalyst includes: a metal oxide catalyst component, wherein the metal oxide catalyst component includes gallium oxide and phase-pure zirconium oxide; and a microporous catalyst component.

[0008] Additional features and advantages will be set forth in the following detailed description, and in part will become apparent to those skilled in the art from the description or may be learned by practicing the embodiments described herein, including the following detailed description and claims.

[0009] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments, and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. DETAILED DESCRIPTION

[0010] Reference will now be made in detail to embodiments of hybrid catalysts and methods for preparing C2 to C4 olefins using the hybrid catalysts. In one embodiment, a method for preparing C2 to C4 olefins comprises: introducing a feed stream comprising hydrogen and a carbon-containing gas into a reaction zone of a reactor, the carbon-containing gas being selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof; and converting the feed stream in the reaction zone into a product stream comprising C2 to C4 olefins in the presence of a hybrid catalyst comprising: a metal oxide catalyst component comprising gallium oxide and phase pure zirconium oxide; and a microporous catalyst component.

[0011] It is known to use a mixed catalyst to convert a feed stream comprising carbon into a desired product, such as C2 to C4 olefins. However, many known mixed catalysts are inefficient because the mixed catalysts show low feed carbon conversion and / or rapid deactivation when used, such as by increasing methane production, which results in low olefin yield and low stability within a given time amount under a given set of operating conditions. On the contrary, the mixed catalyst disclosed and described herein shows high and stable C2 to C4 olefin yields, even if the catalyst run time increases. The composition of this type of mixed catalyst used in the embodiments is discussed below.

[0012] In short, the mixed catalyst is closely coupled to the independent reaction on each independent catalyst in two independent catalysts. In the first step, the feed stream including at least one of hydrogen (H2) and carbon monoxide (CO), carbon dioxide (CO2) or CO and CO2 (e.g., synthesis gas) is converted into intermediates, such as oxygenated hydrocarbons. In subsequent steps, these intermediates are converted into hydrocarbons (mainly short-chain hydrocarbons, such as C2 to C4 olefins). The continuous formation and consumption of the intermediate oxygenated compounds formed by the reaction of the second step in the first step ensure that there is no thermodynamic limitation to the conversion. By carefully selecting the components of the mixed catalyst bed, a high conversion rate of the synthesis gas feed can be achieved.

[0013] Mixed catalyst system comprises metal oxide catalyst component and microporous catalyst component (for example, silicoaluminophosphate or SAPO type molecular sieve component), and the metal oxide catalyst component converts feed stream into oxygenated hydrocarbon, and the microporous catalyst component converts oxygenated hydrocarbon into hydrocarbon. Known mixed catalyst system based on chromium-zinc mixed metal oxide catalyst usually shows a compromise between the initial yield of C2 to C4 olefins and the sustained yield of C2 to C4 olefins as the catalyst running time increases (also referred to as stability). Therefore, a metal oxide catalyst component is needed, and when combined with microporous catalyst component in mixed catalyst method, the metal oxide catalyst component can cause high initial yield and high stability. It should be understood that, as used herein, "metal oxide catalyst component" includes metals in various oxidation states. In certain embodiments, metal oxide catalyst component can include more than one metal oxide, and individual metal oxides in metal oxide catalyst component can have different oxidation states. Therefore, metal oxide catalyst component is not limited to include metal oxides with uniform oxidation state.

[0014] Embodiments of the hybrid catalysts and systems for using the hybrid catalysts disclosed herein include a metal oxide catalyst component comprising: (1) gallium (Ga); and (2) phase pure zirconium oxide (ZrO2). In some embodiments, the phase pure zirconium oxide may be crystalline, and in some embodiments, the phase pure zirconium oxide may be monoclinic crystalline phase pure zirconium oxide. The metal oxide catalyst component is combined with a microporous catalyst component. According to some embodiments, the microporous catalyst component is an 8-MR microporous catalyst component, such as a SAPO-34 molecular sieve.

[0015] The metal oxide catalyst component for mixed catalyst according to each embodiment will now be described.As mentioned above, the metal of the composition of the metal oxide catalyst component of some mixed catalysts is usually used as a combination of zinc (Zn) and chromium (Cr).However, the catalyst (referred to as high temperature methanol synthesis catalyst) comprising zinc and chromium does not have a combination of good olefin yield and good stability when keeping operation for a long time.Although other metal combinations have been used, it has long been believed that zinc and chromium are the most effective metal oxide components for the production of lower olefins, such as C2 to C4 olefins.

[0016] Gallium oxide (gallium oxide (gallia), Ga2O3) is a very effective promoter for catalysts based on palladium, copper or nickel to form methanol. In this type of function, it is believed that when reduced in the presence of hydrogen, gallium oxide forms suboxides and surface hydrides. Ultimately, the reduction process may lead to alloying of Ga metal with the active catalyst component (Pd, Cu or Ni), thereby producing a better performing intermetallic phase (e.g., Pd-Ga). In contrast, gallium oxide and supported gallium oxide show very poor performance in synthesis gas conversion. Further, bulk pure gallium oxide used as the metal oxide component of a mixed catalyst generally produces a high percentage of paraffins. However, it was unexpectedly found that when gallium oxide was combined with phase-pure zirconium oxide, this combination promoted high olefin yields and high process stability of the mixed catalyst.

[0017] As used herein, the zirconium oxide used in the embodiments disclosed and described herein in the metal oxide catalyst component of the mixed catalyst is a "phase pure zirconium oxide," which is defined herein as a zirconium oxide to which no other materials are intentionally added during formation. Thus, a "phase pure zirconium oxide" includes zirconium oxide having minor amounts of components other than zirconium (including oxides other than zirconium oxide) that are unintentionally present in the zirconium oxide as a natural part of the zirconium oxide formation process, such as hafnium (Hf). Thus, as used herein, "zirconia" and "phase pure zirconium oxide" are used interchangeably unless specifically stated otherwise.

[0018] Without being bound by any particular theory, it is believed that the high surface area of ​​zirconia allows the gallium oxide catalyst acting as part of a mixed catalyst to convert carbonaceous components into C2 to C4 olefins. It is believed that gallium oxide and zirconia help activate each other, which results in an increased yield of C2 to C4 olefins.

[0019] Surprisingly, along with the high activity and high selectivity of the unique combination of Ga / ZrO2 components used to prepare hybrid catalysts with molecular sieves, it has been found that such hybrid catalysts including gallium oxide and zirconium oxide as their metal oxide components have improved stability over extended process times. In the examples, crystalline zirconium oxide has also been found to be a particularly effective support for gallium oxide. Furthermore, in some examples, monoclinic zirconium oxide has been found to be a particularly good support for gallium oxide, which provides a very high activity of the combination without compromising the selectivity for C2 to C4 olefins.

[0020] In the embodiments disclosed herein, the composition of the metal oxide catalyst component is represented by the weight percentage of gallium metal relative to pure zirconium oxide (considering the ZrO2 stoichiometry). In one or more embodiments, the composition of the metal oxide catalyst component is represented by the weight of gallium per 100 grams (g) of zirconium oxide. According to various embodiments, the metal oxide catalyst component includes greater than 0.0 g to 30.0 g of gallium per 100 g of zirconium oxide, such as 5.0 g to 30.0 g of gallium per 100 g of zirconium oxide, 10.0 g to 30.0 g of gallium per 100 g of zirconium oxide, 15.0 g to 30.0 g of gallium per 100 g of zirconium oxide, 20.0 g to 30.0 g of gallium per 100 g of zirconium oxide, or 25.0 g to 30.0 g of gallium per 100 g of zirconium oxide. In some embodiments, the metal oxide catalyst component comprises greater than 0.0 g to 25.0 g of gallium per 100 g of zirconium oxide, such as greater than 0.0 g to 20.0 g of gallium per 100 g of zirconium oxide, greater than 0.0 g to 15.0 g of gallium per 100 g of zirconium oxide, greater than 0.0 g to 10.0 g of gallium per 100 g of zirconium oxide, or greater than 0.0 g to 5.0 g of gallium per 100 g of zirconium oxide. In some embodiments, the metal oxide catalyst component comprises 5.0 g to 25.0 g of gallium per 100 g of zirconium oxide, such as 10.0 g to 20.0 g of gallium per 100 g of zirconium oxide. In some embodiments, the metal oxide catalyst component comprises 0.01 g to 5.00 g of gallium per 100 g of zirconium oxide, such as 0.50 g to 5.00 g of gallium per 100 g of zirconium oxide, 1.00 g to 5.00 g of gallium per 100 g of zirconium oxide, 1.50 g to 5.00 g of gallium per 100 g of zirconium oxide, 2.00 g to 5.00 g of gallium per 100 g of zirconium oxide, g gallium to 100g zirconia, 2.50g gallium to 5.00g gallium per 100g zirconia, 3.00g gallium to 5.00g gallium per 100g zirconia, 3.50g gallium to 5.00g gallium per 100g zirconia, 4.00g gallium to 5.00g gallium per 100g zirconia or 4.50g gallium to 5.00g gallium per 100g zirconia.

[0021] As disclosed above, and without being bound by any particular theory, it is understood that the high surface area zirconium oxide acts as a support or carrier for the gallium component of the metal oxide component, which produces a gallium and zirconium oxide metal oxide catalyst component that will have selectivity for preparing C2 to C4 olefins. Therefore, it has been discovered that a process for preparing a gallium and zirconium oxide metal oxide catalyst that requires intimate contact of the gallium and zirconium components produces a metal oxide catalyst component with improved selectivity for C2 to C4 olefins.

[0022] In view of the above, a method for preparing the gallium and zirconium metal oxide components of the mixed catalyst is by incipient wetness impregnation. In this method, an aqueous mixture of a gallium precursor material (which in an embodiment may be gallium nitrate (Ga(NO3)3)) is added to the zirconium oxide particles in a certain dosage (e.g., dropwise) while the zirconium oxide particles are vigorously shaken. It should be understood that the total amount of gallium precursor mixed with the zirconium oxide particles will be determined according to the desired target amount of gallium in the metal oxide catalyst component.

[0023] As previously discussed, according to some embodiments, the zirconium oxide particles include zirconium oxide particles having a crystalline structure. In an embodiment, the zirconium oxide particles include zirconium oxide particles having a monoclinic structure. In one or more embodiments, the zirconium oxide particles consist essentially of or consist of crystalline zirconium oxide particles, and in some embodiments, the zirconium oxide particles consist essentially of or consist of monoclinic zirconium oxide particles. According to some embodiments, the zirconium oxide particles have a BET surface area greater than or equal to 5 square meters per gram (m 2 / g), if greater than 10m 2 / g, greater than 20m 2 / g, greater than 30m 2 / g, greater than 40m 2 / g, greater than 50m 2 / g, greater than 60m 2 / g, greater than 70m 2 / g, greater than 80m 2 / g, greater than 90m 2 / g, greater than 100m 2 / g, greater than 110m 2 / g, greater than 120m 2 / g, greater than 130m 2 / g or greater than 140m 2 According to some embodiments, the maximum BET surface area of ​​the zirconium oxide particles is 150 m 2 / g. Therefore, in some embodiments, the BET surface area of ​​the zirconium oxide particles is 5m 2 / g to 150m 2 / g, 10m2 / g to 150m 2 / g, 20m 2 / g to 150m 2 / g, such as 30m 2 / g to 150m 2 / g, 40m 2 / g to 150m 2 / g, 50m 2 / g to 150m 2 / g, 60m 2 / g to 150m 2 / g, 70m 2 / g to 150m 2 / g, 80m 2 / g to 150m 2 / g, 90m 2 / g to 150m 2 / g、100m 2 / g to 150m 2 / g, 110m 2 / g to 150m 2 / g, 120m 2 / g to 150m 2 / g, 130m 2 / g to 150m 2 / g or 140m 2 / g to 150m 2 / g. In some embodiments, the BET surface area of ​​the zirconium oxide particles is 5m 2 / g to 140m 2 / g, such as 5m 2 / g to 130m 2 / g, 5m 2 / g to 120m 2 / g, 5m 2 / g to 110m 2 / g, 5m 2 / g to 100m 2 / g, 5m 2 / g to 90m 2 / g, 5m 2 / g to 80m 2 / g, 5m 2 / g to 70m 2 / g, 5m 2 / g to 60m 2 / g, 5m 2 / g to 50m 2 / g, 5m 2 / g to 40m 2 / g, 5m 2 / g to 30m 2 / g, 5m 2 / g to 20m 2 / g or 5m 2 / g to 10m 2 In some embodiments, the BET surface area of ​​the zirconium oxide particles is 10 m 2 / g to 140m 2 / g, 20m 2 / g to 130m 2 / g, 30m 2 / g to 120m 2 / g, 40m 2 / g to 110m 2 / g, 50m 2 / g to 100m 2 / g, 60m 2 / g to 90m 2 / g or 70m 2 / g to 80m 2 / g.

[0024] Once the gallium precursor and zirconium oxide particles are thoroughly mixed, the metal oxide catalyst component can be dried at a temperature below 200 degrees Celsius (° C.), such as below 175° C. or below 150° C. After drying, the metal oxide catalyst component is calcined at a temperature of 400° C. to 800° C., such as 425° C. to 775° C., 450° C. to 750° C., 475° C. to 725° C., 500° C. to 700° C., 525° C. to 675° C., 550° C. to 650° C., 575° C. to 625° C., or about 600° C. After calcination, the composition of the mixed metal oxide catalyst component is determined and reported as elemental gallium referenced as previously disclosed per 100 g of phase-pure zirconium oxide (simplified to the stoichiometry of ZrO2).

[0025] In an embodiment, the metal oxide catalyst component can be prepared by mixing a powder or slurry of a gallium precursor (such as gallium nitrate or gallium oxide) and zirconium oxide. According to some embodiments, the zirconium oxide particles include zirconium oxide particles having a crystalline structure. In an embodiment, the zirconium oxide particles include zirconium oxide particles having a monoclinic structure. In one or more embodiments, the zirconium oxide particles are essentially composed of crystalline zirconium oxide particles or are composed of crystalline zirconium oxide particles, and in some embodiments, the zirconium oxide particles are essentially composed of monoclinic zirconium oxide particles or are composed of monoclinic zirconium oxide particles. In an embodiment, the zirconium oxide particles have a BET surface area disclosed above. The powder or slurry can be vigorously mixed at an elevated temperature, such as room temperature (approximately 23°C) to 100°C. After the powder or slurry is thoroughly mixed, the metal oxide catalyst component can be dried and calcined at a temperature of 400° C. to 800° C., such as 425° C. to 775° C., 450° C. to 750° C., 475° C. to 725° C., 500° C. to 700° C., 525° C. to 675° C., 550° C. to 650° C., 575° C. to 625° C., or about 600° C. After calcination, the composition of the mixed metal oxide catalyst component is determined and reported as the weight of elemental gallium relative to 100 g of phase-pure zirconium oxide as disclosed above (simplified to the stoichiometry of ZrO2).

[0026] It should be understood that, according to various embodiments, the metal oxide catalyst component can be prepared by other methods that ultimately result in intimate contact between gallium and zirconium oxide. Some non-limiting examples include vapor deposition of a Ga-containing precursor (organic or inorganic in nature) followed by controlled decomposition thereof. Similarly, the method used to disperse liquid gallium metal can be modified by those skilled in the art to develop Ga-ZrO2.

[0027] In some embodiments, elements other than zirconium oxide and gallium may be present in the metal oxide catalyst component containing phase-pure zirconium oxide and gallium. Such elements may be introduced into the phase-pure zirconium oxide before, during, or after the gallium is introduced into the composition. Sometimes, such elements are added to guide and stabilize the crystallization of the zirconium oxide phase (e.g., Y-stabilized tetragonal ZrO2). In other cases, additional elements from the group of rare earths, alkali metals, and / or transition metals are co-deposited with the gallium precursor or introduced only when the Ga-ZrO2 mixed composition has been first prepared. Similarly, the metal oxide catalyst component may also contain residues or be purposefully modified with non-metallic dopants, such as sulfur (present as, for example, oxygen-containing anions SO4), chlorine (Cl), phosphorus (P), or mixtures thereof, which may be present in the zirconium oxide support or retained after being used as an element intended to be a precursor for the introduction of gallium or other metals into the phase-pure zirconium oxide.

[0028] In one or more embodiments, after the metal oxide catalyst component has been formed, for example, by the method disclosed above, the metal oxide catalyst component is physically mixed with the microporous catalyst component. In an embodiment, the microporous catalyst component is selected from a molecular sieve having an 8-MR pore opening and having a framework type selected from the group consisting of the following framework types: CHA, AEI, AFX, ERI, LTA, UFI, RTH, EDI, GIS, MER, RHO and combinations thereof, the framework type corresponding to the naming convention of the International Zeolite Association. It should be understood that in an embodiment, both aluminosilicate and silicoaluminophosphate frameworks can be used. Some embodiments may include tetrahedral aluminosilicates, ALPO (e.g., tetrahedral aluminophosphates), SAPO (e.g., tetrahedral silicoaluminophosphates) and only silica-based framework silicates. In certain embodiments, the microporous catalyst component may be a silicoaluminophosphate with a chabazite (CHA) framework type. Examples of these may include but are not necessarily limited to: CHA embodiments selected from SAPO-34 and SSZ-13; and AEI embodiments, such as SAPO-18. A combination of microporous catalyst components with any of the above framework types can also be used. It should be understood that, depending on the desired product, the microporous catalyst component can have different ring pore openings. For example, depending on the desired product, a microporous catalyst component with 8-MR to 12-MR pore openings can be used. However, in order to produce C2 to C4 olefins, a microporous catalyst component with 8-MR pore openings is used in the embodiments.

[0029] The metal oxide catalyst component and the microporous catalyst component of the mixed catalyst can be mixed together in any suitable manner, such as by physical mixing, such as shaking, stirring or other agitation. In an embodiment, the metal oxide catalyst component can account for 1.0 wt% to 99.0 wt% of the mixed catalyst, such as 5.0 wt% to 99.0 wt%, 10.0 wt% to 99.0 wt%, 15.0 wt% to 99.0 wt%, 20.0 wt% to 99.0 wt%, 25.0 wt% to 99.0 wt%, 30.0 wt% to 99.0 wt%, 35.0 wt% to 99.0 wt%, 40.0 wt% to 99.0 wt%, 45.0 wt% to 99.0 wt%, 50.0 wt% to 99.0 wt%, 51.0 wt% to 99.0 wt%, 52.0 wt% to 99.0 wt%, 53.0 wt% to 99.0 wt%, 54.0 wt% to 99.0 wt%, 55.0 wt% to 99.0 wt%, 56.0 wt% to 99.0 wt%, 57.0 wt% to 99.0 wt%, 58.0 wt% to 99.0 wt%, 59.0 wt% to 99.0 wt%, 60.0 wt% to 99.0 wt%, 61.0 wt% to 99.0 wt%, 62.0 wt% to 99.0 wt%, 64.0 wt% to 99.0 wt%, 65.0 wt% to 99.0 wt%, 66.0 wt% to 99.0 wt%, 67.0 wt% to wt% to 99.0wt%, 50.0wt% to 99.0wt%, 55.0wt% to 99.0wt%, 60.0wt% to 99.0wt%, 65.0wt% to 99.0wt%, 70.0wt% to 99.0wt%, 75.0wt% to 99.0wt%, 80.0wt% to 99.0wt%, 85.0wt% to 99.0wt%, 90.0wt% to 99.0wt% or 95.0wt% to 99.0wt%. In some embodiments, the metal oxide catalyst component comprises 1.0 wt % to 95.0 wt %, such as 1.0 wt % to 90.0 wt %, 1.0 wt % to 85.0 wt %, 1.0 wt % to 80.0 wt %, 1.0 wt % to 75.0 wt %, 1.0 wt % to 70.0 wt %, 1.0 wt % to 65.0 wt %, 1.0 wt % to 60.0 wt %, 1.0 wt % to 55.0 wt %. .0wt%, 1.0wt% to 50.0wt%, 1.0wt% to 45.0wt%, 1.0wt% to 40.0wt%, 1.0wt% to 35.0wt%, 1.0wt% to 30.0wt%, 1.0wt% to 25.0wt%, 1.0wt% to 20.0wt%, 1.0wt% to 15.0wt%, 1.0wt% to 10.0wt% or 1.0wt% to 5.0wt%. In some embodiments, the metal oxide catalyst component accounts for 5.0wt% to 95.0wt% of the mixed catalyst, such as 10.0wt% to 90.0wt%, 15.0wt% to 85.0wt%, 20.0wt% to 80.0wt%, 25.0wt% to 75.0wt%, 30.0wt% to 70.0wt%, 35.0wt% to 65.0wt%, 40.0wt% to 60.0wt% or 45.0wt% to 55.0wt%.

[0030] After the metal oxide catalyst component has been formed and combined with the microporous catalyst component to form a hybrid catalyst, the hybrid catalyst can be used in a process for converting carbon in a carbonaceous feed stream into C2 to C4 olefins. Such a process will be described in more detail below.

[0031] According to various embodiments, a feed stream is fed into a reaction zone, the feed stream comprising hydrogen (H2) and a carbon-containing gas selected from carbon monoxide (CO), carbon dioxide (CO2), and combinations thereof. In some embodiments, the H2 gas is present in the feed stream in an amount of 10 volume percent (vol%) to 90 vol%, based on the combined volume of the H2 gas and the gas selected from CO, CO2, and combinations thereof. The feed stream is contacted with a mixed catalyst as disclosed and described herein in the reaction zone. The mixed catalyst comprises a metal oxide catalyst component comprising gallium oxide and zirconium oxide; and a microporous catalyst component.

[0032] It is understood that the activity of the mixed catalyst will be higher for feed streams containing CO as the carbon-containing gas, and the activity of the mixed catalyst will decrease when a larger portion of the carbon-containing gas in the feed stream is CO. However, this is not to say that the mixed catalyst disclosed and described herein cannot be used in a process in which the feed stream includes CO as all or a majority of the carbon-containing gas.

[0033] The feed stream is contacted with the mixed catalyst in a reaction zone under reaction conditions sufficient to form a product stream comprising C2 to C4 olefins. According to one or more embodiments, the reaction conditions include a temperature in the reaction zone ranging from 300° C. to 500° C., such as 300° C. to 475° C., 300° C. to 450° C., 300° C. to 425° C., 300° C. to 400° C., 300° C. to 375° C., 300° C. to 350° C., or 300° C. to 325° C. In other embodiments, the temperature in the reaction zone is 325° C. to 500° C., 350° C. to 500° C., 375° C. to 500° C., 400° C. to 500° C., 425° C. to 500° C., 450° C. to 500° C., or 475° C. to 500° C. In yet other embodiments, the temperature within the reaction zone is 300°C to 500°C, such as 325°C to 475°C, 350°C to 450°C, or 360°C to 440°C.

[0034] In embodiments, the reaction conditions further comprise a pressure within the reaction zone of at least 1 bar (100 kilopascals (kPa), such as at least 5 bar (500 kPa), at least 10 bar (1,000 kPa), at least 15 bar (1,500 kPa), at least 20 bar (2,000 kPa), at least 25 bar (2,500 kPa), at least 30 bar (3,000 kPa), at least 35 bar (3,500 kPa), at least 40 bar (4,000 kPa), at least 45 bar (4,500 kPa), at least 50 bar (500 kPa), at least 55 bar (500 kPa), at least 50 bar (600 kPa), at least 50 bar (600 kPa), at least 55 bar (600 kPa), at least 50 bar (7 ... kPa), at least 50 bar (5,000 kPa), at least 55 bar (5,500 kPa), at least 60 bar (6,000 kPa), at least 65 bar (6,500 kPa), at least 70 bar (7,000 kPa), at least 75 bar (7,500 kPa), at least 80 bar (8,000 kPa), at least 85 bar (8,500 kPa), at least 90 bar (9,000 kPa), at least 95 bar (9,500 kPa), or at least 100 bar (10,000 kPa). In other embodiments, the reaction conditions include a pressure within the reaction zone of 5 bar (500 kPa) to 100 bar (10,000 kPa), such as 10 bar (1,000 kPa) to 95 bar (9,500 kPa), 15 bar (1,500 kPa) to 90 bar (9,000 kPa), 20 bar (2,000 kPa) to 85 bar (8,500 kPa), 25 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3,000 kPa) to 40 bar (5,000 kPa), 50 bar (6,000 kPa) to 60 bar (7,000 kPa), 70 bar (8,000 kPa) to 85 bar (8,500 kPa), 80 bar (9,000 kPa) to 90 bar (9,000 kPa), 100 bar (10,000 kPa) to 100 bar (10,000 kPa), 150 bar (1,500 kPa) to 90 bar (9,000 kPa), 20 bar (2,000 kPa) to 85 bar (8,500 kPa), 25 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3,000 kPa) to 100 bar (10,000 kPa), 100 bar (1 In some embodiments, the pressure inside the reaction zone is from 20 bar (2,000 kPa) to 60 bar (6,000 kPa).

[0035] According to various embodiments, the gas hourly space velocity (GHSV) in the reaction zone is 1,200 per hour ( / hour) to 12,000 / hour, such as 1,500 / hour to 10,000 / hour, 2,000 / hour to 9,500 / hour, 2,500 / hour to 9,000 / hour, 3,000 / hour to 8,500 / hour, 3,500 / hour to 8,000 / hour, 4,000 / hour to 7,500 / hour, 4,500 / hour to 7,000 / hour, 5,000 / hour to 6,500 / hour or 5,500 / hour to 6,000 / hour. In some embodiments, the GHSV within the reaction zone is 1,800 / hour to 3,600 / hour, such as 2,000 / hour to 3,600 / hour, 2,200 / hour to 3,600 / hour, 2,400 / hour to 3,600 / hour, 2,600 / hour to 3,600 / hour, 2,800 / hour to 3,600 / hour, 3,000 / hour to 3,600 / hour, 3,200 / hour to 3,600 / hour, or 3,400 / hour to 3,600 / hour. In some embodiments, the GHSV within the reaction zone is 1,800 / hour to 3,400 / hour, such as 1,800 / hour to 3,200 / hour, 1,800 / hour to 3,000 / hour, 1,800 / hour to 2,800 / hour, 1,800 / hour to 2,600 / hour, 1,800 / hour to 2,400 / hour, 1,800 / hour to 2,200 / hour, or 1,800 / hour to 2,000 / hour. In some embodiments, the GHSV within the reaction is 2,000 / hour to 3,400 / hour, such as 2,200 / hour to 3,200 / hour, 2,400 / hour to 3,000 / hour, or 2,600 / hour to 2,800 / hour.

[0036] By using the mixed catalysts disclosed and described herein and the process conditions disclosed and described herein, improved C2 to C4 olefin yields and carbon conversions can be achieved. For example, in embodiments, wherein the ratio of hydrogen to carbon monoxide H2 / CO ranges from 2 to 5, such as greater than 2.2 and less than 3.8 or greater than 2.8 and less than 3.4, wherein the temperature ranges from 360°C to 460°C, such as 380°C to 440°C or 400°C to 420°C, and the pressure ranges from 5 to 100 bar, such as 20 to 80 bar or 30 to 60 bar. Using such conditions, the C2 to C4 olefin yield is greater than or equal to 4.0 mol%, such as greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 10.0 mol%, greater than or equal to 12.0 mol%, greater than or equal to 15.0 mol%, greater than or equal to 17.0 mol%, greater than or equal to 20.0 mol%, greater than or equal to 22.0 mol%, greater than or equal to 25.0 mol%, greater than or equal to 27.0 mol%, greater than or equal to 30.0 mol%, greater than or equal to 32.0 mol%, or greater than or equal to 35.0 mol%. In some embodiments, the maximum C2 to C4 olefin yield is 50.0 mol%. Thus, in some embodiments, the C2 to C4 olefin yield is greater than or equal to 4.0 mol% to 50.0 mol%, such as 5.0 mol% to 50.0 mol%, 7.0 mol% to 50.0 mol%, 10.0 mol% to 50.0 mol%, 12.0 mol% to 50.0 mol%, 15.0 mol% to 50.0 mol%, 17.0 mol% to 50.0 mol%, 20.0 mol% to 50.0 mol%, 22.0 mol% to 50.0 mol%, %, 1%, 25.0 mol% to 50.0 mol%, 27.0 mol% to 50.0 mol%, 30.0 mol% to 50.0 mol%, 32.0 mol% to 50.0 mol%, 35.0 mol% to 50.0 mol%, 37.0 mol% to 50.0 mol%, 40.0 mol% to 50.0 mol%, 42.0 mol% to 50.0 mol%, 45.0 mol% to 50.0 mol% or 47.0 mol% to 50.0 mol%.

[0037] In embodiments, the carbon conversion rate can be improved using the mixed catalyst disclosed and described herein and the process conditions disclosed and described herein. Within the disclosed process range, the conversion of the feed containing carbon oxides and hydrogen can be carried out in a series of reactors, wherein the water by-product is separated intermediately by means of, for example, phase separation, membrane separation or some type of water selective absorption process. Further continuously directing the partially converted and anhydrous effluent to subsequent reactors and repeating this technical operation mode will have the overall effect of improving olefin yield. For example, in embodiments where two to four such operations are performed, the total olefin yield can be greater than or equal to 50.0 mol%, such as greater than or equal to 52.0 mol%, greater than or equal to 55.0 mol%, greater than or equal to 57.0 mol%, greater than or equal to 60.0 mol%, greater than or equal to 62.0 mol%, greater than or equal to 65.0 mol%, greater than or equal to 67.0 mol%, greater than or equal to 70.0 mol%, greater than or equal to 72.0 mol%, greater than or equal to 75.0 mol%, greater than or equal to 77.0 mol%, greater than or equal to 80.0 mol%, or greater than or equal to 85.0 mol%. In some embodiments, the maximum carbon conversion is 95.0 mol%. Therefore, in an embodiment, the carbon conversion rate can be greater than or equal to 50.0 mol% to 95.0 mol%, such as 52.0 mol% to 95.0 mol%, 55.0 mol% to 95.0 mol%, 57.0 mol% to 95.0 mol%, 60.0 mol% to 95.0 mol%, 62.0 mol% to 95.0 mol%, 65.0 mol% to 95.0 mol%, 67.0 mol% to 95.0 mol%, 60.0 mol% to 95.0 mol%, % to 95.0 mol%, 72.0 mol% to 95.0 mol%, 75.0 mol% to 95.0 mol%, 77.0 mol% to 95.0 mol%, 80.0 mol% to 95.0 mol%, 82.0 mol% to 95.0 mol%, 85.0 mol% to 95.0 mol%, 87.0 mol% to 95.0 mol%, 90.0 mol% to 95.0 mol% or 92.0 mol% to 95.0 mol%.

[0038] Examples

[0039] Embodiment is further illustrated by following example and comparative example.In all examples and comparative example, mixed catalyst is prepared by mixing a given amount of mixed oxide catalyst component (60-80 mesh) with microporous catalyst component SAPO-34 (60-80 mesh).Described amount can be found in the following table.However, it should be understood that in some comparative examples, SAPO-34 is not included.This is indicated by zero value (" 0 ") in the following table.

[0040] Comparative Example 1

[0041] Composite catalysts having a SAPO-34 microporous catalyst component and bulk In2O3, bulk Ga2O3 or bulk ZrO2; physical mixtures of bulk Ga2O3 and ZrO2 without a microporous catalyst component.

[0042] Table 1a shows the results of a process for converting syngas to olefins under the following process conditions: H2 / CO is about 2.0; pressure is 20 bar (2,000 kPa); temperature is 390°C, and GHSV is equal to 1200 / hour. The metal oxide catalysts used in the comparative examples are bulk metal oxides as shown in Table 1a. The indium oxide used in this comparative example is commercially available from Aldrich with product number 632317, and the gallium oxide used is commercially available from Aldrich with product number 20,333-5. Prior to this test, each of the starting components was compacted, crushed and sized to provide a 60-80 mesh fraction in order to prepare a physical mixture. Next, a mixed catalyst was prepared by combining 150 μL of SAPO-34 (approximately 100 μL of particles of a specific size) and adding 150 μL of indium oxide or gallium oxide (each approximately 100 μL of particles of a specific size), after gently shaking the particles together in a vial. The following table references the catalytic performance of a dual particle bed of SAPO-34 mixed with either pure oxide containing weights of each component.

[0043] Table 1a

[0044]

[0045] Table 1a continued

[0046]

[0047] Table 1b shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3.0; pressure is 40 bar (4,000 kPa); temperature is 420°C; and GHSV is equal to 2400 / hour and compares the intrinsic properties of zirconium oxide or gallium oxide mixed with SAPO-34. The zirconium oxide used in this comparative example is commercially available monoclinic ZrO2 (supplier NORPRO, product code SZ39114) and contains some Hf impurities (about 2.45 wt%). Before use, the zirconium oxide was dispersed in water, dried, and calcined at 550°C. The gallium oxide used in this comparative example is commercially available gallium oxide (available as Alfa Aesar, product number 10508). Before use, the gallium oxide was dispersed in water, dried, and calcined at 550°C. Prior to this test, both the oxide and the sieve were compacted, crushed, and sieved to provide a starting component of a 60-80 mesh fraction. Next, the mixed catalyst was prepared by volume measuring approximately 200 μL of SAPO-34 (specific size particles) and adding 200 μL of zirconium oxide (specific size particles) or 200 μL of gallium oxide (specific size particles) after gentle shaking. The following table references the catalytic performance of a double particle bed of SAPO-34 mixed with either pure oxide.

[0048] Table 1b

[0049]

[0050] Table 1b continued

[0051]

[0052] Table 1c shows the results of a process for converting synthesis gas to CO under the following process conditions: H2 / CO is about 3.0; pressure is 40 bar (4,000 kPa); temperature is 420°C; and GHSV is equal to 2400 / hour. To prepare the dual particle catalyst bed, zirconium oxide (20 mg) and gallium oxide (80 mg) were physically mixed together to form a mixture of particles (100 mg). To prepare this combination, the ZrO2 and Ga2O3 materials mentioned in Example 1b were used. To further distinguish this combination, the catalyst bed did not contain any SAPO-34 component.

[0053] Table 1c

[0054]

[0055] Table 1c continued

[0056]

[0057] Comparative Example 1a demonstrates the inherent properties of pure bulk oxides of elements from Group 13 of the Periodic Table when formulated with SAPO-34 in a dual particle bed. Comparative Example 1b benchmarks the inherent properties of pure zirconium oxide versus pure gallium in combination with SAPO-34 in a dual particle bed application. This comparative example shows that different pure oxides in combination with SAPO-34 result in very different catalytic behaviors for the conversion of syngas to hydrocarbons. Notably, (1) pure In2O3 has some initial high activity and selectivity for olefins, but a short process life, and the mixed system deactivates quite quickly; (2) pure monoclinic ZrO2 shows high selectivity for olefins and a long operating life, but poor activity; (3) pure Ga2O3 shows moderate activity and very poor selectivity for olefins and high selectivity for paraffins compared to indium oxide, and can simultaneously convert syngas over long process times. In addition, Comparative Example 1c shows that a physical mixture of gallium oxide and zirconium oxide (SAPO-34) without a microporous catalyst component also has poor activity and low selectivity for olefins.

[0058] Comparative Example 2

[0059] Table 2a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 2; temperature is 390°C; pressure is 20 bar (2,000 kPa); and GHSV is equal to 1200 / hour. The mixed catalyst was prepared from specific size (60-80 mesh) particles of SAPO-34 (150 μL volume of specific size particles or about 75 mg at a time) and specific size particles of various mixed metal oxide catalysts. The mixed oxides are characterized by gallium and lack zirconium. The oxides are prepared by incipient wetness impregnation of an aqueous solution of a gallium nitrate precursor onto oxides of silicon, titanium or niobium, followed by drying and calcination (500 dig). The amount of specific size 60-80 mesh mixed oxide particles used to prepare the mixed catalyst bed with SAPO-34 was about 150 μL volume measurement at a time. Due to the different apparent densities of the different support oxides, the weights of the oxides are also different. The mixed catalysts were prepared after gently shaking the specific size particles together in a vial.

[0060] Table 2a

[0061]

[0062] Table 2a continued

[0063]

[0064] Table 2b shows the results of the process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3; temperature is 420°C; pressure is 40 bar (4,000 kPa); and GHSV is equal to 2400 / hour. The amount of 60-80 mesh mixed oxide particles of a specific size used to prepare the mixed catalyst bed with SAPO-34 was measured in approximately 200 μL volume each time. The mixed catalyst was prepared after gently shaking the particles of a specific size together in a vial.

[0065] Table 2b

[0066]

[0067] Table 2b continued

[0068]

[0069] For composite catalysts with SAPO-34 as microporous catalyst component and Ga-MOx metal oxide catalyst component. Each of the Ga-MOx metal oxide catalyst components is prepared by processing crystalline powders of Y2O3, La2O3, CeO2, Cr2O3, MgAl2O4 or MgO and Ga2O3 in the form of slurry fine particles in deionized water, drying, and calcining at 550°C.

[0070] Table 2c shows the results of the process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3; temperature is 420°C; pressure is 40 bar (4,000 kPa); and GHSV is equal to 2400 / hour. The amount of 60-80 mesh mixed oxide particles of a specific size used to prepare the mixed catalyst bed with SAPO-34 was measured in approximately 200 μL volume each time. The mixed catalyst was prepared after gently shaking the particles of a specific size together in a vial.

[0071] Table 2c

[0072]

[0073] Table 2c continued

[0074]

[0075] Table 2c continued

[0076]

[0077] Example 1

[0078] This example shows that the catalyst is composed of a SAPO-34 microporous catalyst component and a ZrO2-supported gallium catalyst (monoclinic ZrO2 with a BET surface area of ​​about 50 m 2The amount of mixed oxide particles of a specific size of 60-80 mesh used to prepare the mixed catalyst bed is reported in Tables 3a and 3b. The mixed catalyst was prepared after gently shaking the particles together in a vial.

[0079] Table 3a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 2; temperature is 390°C; pressure is 20 bar (2,000 kPa); and GHSV is equal to 1200 / hour.

[0080] Table 3a

[0081]

[0082] Table 3a continued

[0083]

[0084] Table 3b shows the results of a process for converting synthesis gas to olefins under the following process conditions: synthesis gas process H2 / CO is about 3; temperature is 420°C; pressure is 40 bar; and GHSV is equal to 2400 / hour.

[0085] Table 3b

[0086]

[0087] Table 3b continued

[0088]

[0089] Example 1 demonstrates that Ga-ZrO2 microporous was prepared at different loadings deposited on monoclinic zirconia and tested with SAPO-34 as the microporous catalyst component under different feed conditions (H2 / CO of about 2 or about 3) and processes (temperature and pressure). This example demonstrates the effectiveness of lower Ga loadings in the metal oxide catalyst component and the effectiveness of the zirconia support.

[0090] Example 2

[0091] This example comprises SAPO-34 as the microporous catalyst component and ZrO2-supported gallium as the metal oxide catalyst component (monoclinic ZrO2 with a BET surface area of ​​approximately 100 m 2 The amount of the mixed oxide particles of a specific size of 60-80 mesh used to prepare the mixed catalyst bed is reported in Tables 4a and 4b. The mixed catalyst was prepared after gently shaking the particles together in a vial.

[0092] Table 4a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 2; temperature is 390°C; pressure is 20 bar (2,000 kPa); and GHSV is equal to 1200 / hour.

[0093] Table 4a

[0094]

[0095] Table 4a continued

[0096]

[0097] Table 4b shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3; temperature is 420°C; pressure is 40 bar (4,000 kPa); and GHSV is equal to 2400 / hour.

[0098] Table 4b

[0099]

[0100] Table 4b continued

[0101]

[0102] Example 2 further demonstrates that Ga deposited on monoclinic zirconia can achieve very high composite catalyst olefin yields over a variety of syngas feeds (2, 3) and process conditions. Very low Ga loadings can result in high surface area for the active material of monoclinic ZrO2.

[0103] Example 3

[0104] This example comprises SAPO-34 as the microporous catalyst component and a gallium catalyst supported on ZrO2 (tetragonal ZrO2 with a BET surface area of ​​approximately 130 m 2 The amount of the mixed oxide particles of a specific size of 60-80 mesh used to prepare the mixed catalyst bed is reported in Tables 5a and 5b. The mixed catalyst was prepared after gently shaking the particles together in a vial.

[0105] Table 5a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 2; temperature is 390°C; pressure is 20 bar (2,000 kPa); and GHSV is equal to 1200 / hour.

[0106] Table 5a

[0107]

[0108] Table 5a continued

[0109]

[0110] Table 5b shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3; temperature is 420°C; pressure is 40 bar (4,000 kPa); and GHSV is equal to 2400 / hour.

[0111] Table 5b

[0112]

[0113] Table 5b continued

[0114]

[0115] This example demonstrates that Ga deposited on tetragonal zirconia is an active component of the catalyst composite (dual particle bed). However, with respect to the operation shown in Example 2, the overall performance is inferior to that of Ga-ZrO2 prepared on monoclinic ZrO2.

[0116] Example 4

[0117] This example comprises a mixed catalyst characterized by a gallium metal oxide catalyst component supported on ZrO2, which also includes other elements in the zirconia support and / or co-impregnated with a gallium precursor. In the first example (Table 6a), the zirconia support is identified as tetragonal zirconia (NORPRO, product number: SZ61156, containing approximately 7.3 g La per 100 g ZrO2) containing some lanthanum (La). Gallium is impregnated onto this support alone or co-impregnated with an additional amount of lanthanum. The latter case is evidenced by the increased amount of La in the sample (first and second entries in the table). The amount of mixed oxide particles of a specific size of 60-80 mesh used to prepare the mixed catalyst bed is reported in Table 6a. The mixed catalyst is prepared after gently shaking the particles together in a vial.

[0118] Table 6a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO = 3; temperature, 390°C; pressure, 30 bar; and GHSV equal to 1200 / hour.

[0119] Table 6a

[0120]

[0121] Table 6a continued

[0122]

[0123] Table 6b shows the results of the process for the conversion of carbon monoxide and carbon dioxide (COx conversion) into olefins under the following process conditions: H2 / CO / CO2 equal to 69.1 / 13.6 / 6.9 vol%; temperature is 390°C; pressure is 30 bar, GHSV equal to 1200 / hour. Along with the catalytic materials mentioned in Table 6a, the tests further comprised additional samples prepared on a zirconia support identified as tetragonal zirconia containing some tungsten (W) (NORPRO, product number: SZ61143, containing about 11 wt% of W). Ga precursors were impregnated onto this support alone or co-impregnated with La precursors (third and fourth entries in Table 6b).

[0124] Table 6b

[0125]

[0126] Table 6b continued

[0127]

[0128] Example 4 demonstrates that Ga deposited on tetragonal zirconia with La in a support is an active and stable composite catalyst. In contrast, the presence of W in tetragonal zirconia significantly impairs its catalytic behavior. Co-impregnated La can mitigate some of the adverse effects of the presence of W (i.e., the effect on methane selectivity).

[0129] Example 5

[0130] This example comprises a catalyst having a SAPO-34 microporous catalyst component and featuring a ZrO2-supported gallium / lanthanum catalyst. As a support for the preparation of the latter, a commercial sample of monoclinic ZrO2 (NORPRO, product number: SZ31108, with a BET surface area of ​​approximately 70 m 2 The catalysts were tested in long-term process runs under various process conditions.

[0131] Table 7a shows the result of converting synthesis gas into olefins for a kind of mixed catalyst in process research, and process conditions change with process time during the process research.When two components of 60-80 purpose particles of specific size are gently shaken together in a vial, mixed catalyst is prepared by 123mg of SAPO-34 component and 185mg of mixed Ga-La / ZrO mixed oxide component.The average catalytic result of each process section is reported and the beginning and end (minimum ToS [hours]–maximum ToS [hours]) of each process section are included.Note that the running time is counted from the beginning of exposure to synthesis gas.Each process section has different process operation parameters, such as H2 / CO ratio and space velocity, and the temperature and pressure of process remain constant simultaneously.

[0132] Table 7a

[0133]

[0134] Table 7a continued

[0135]

[0136] Table 7b shows the results of a process for converting synthesis gas into olefins under the following process conditions: H2 / CO is about 3; temperature is 390 to 400°C; pressure is equal to 30 bar; and GHSV is equal to 1200 / hour to 2400 / hour.

[0137] Table 7b shows the result of converting synthesis gas into olefins for mixed catalyst in long-term process research, wherein process conditions are along with process time variation.When two components of 60-80 purpose particles of specific size are gently shaken together in a vial, by 147mg of SAPO-34 component and 130mg of mixed Ga-La / ZrO mixed oxide component prepares mixed catalyst.The average catalytic result of each process section is reported and comprises the beginning and end (minimum ToS [hours]–maximum ToS [hours]) of each process section.Note, count the running time from the beginning of exposure to synthesis gas.Each process section has different process operation parameters, such as H2 / CO ratio, space velocity or temperature, and the pressure of process remains constant (30 bar) simultaneously.

[0138] Table 7b

[0139]

[0140] Table 7b continued

[0141]

[0142] Example 5 demonstrates that Ga / La-ZrO2 can maintain olefins processing with high olefin yields from syngas for extended periods of time and under a variety of process (p, T, GHSV) conditions.

[0143] Example 6

[0144] This example comprises a mixed catalyst with a SAPO-34 microporous catalyst component, which is characterized by a Ga-ZrO metal oxide catalyst component. The example compares semi-crystalline coprecipitated mixed oxide Ga-ZrO (synthetic method for replacing impregnation), wherein there may be closely connected-Ga-ZrO, but ZrO shows poor crystallinity, effectively deteriorating the catalyst system. The example also compares the monoclinic ZrO processed by slurry and calcined crystallization and the Ga-ZrO prepared by a Ga precursor in the form of Ga O (synthetic method for replacing impregnation), wherein the crystalline powder produces the desired catalytic effect. In addition, it is compared with the physical mixture of closely connected powders without any processing to produce Ga O and ZrO, wherein the mixed system with SAPO-34 shows undeveloped catalytic performance. The amount of 60-80 purpose mixed oxide particles of a specific size for preparing a mixed catalyst bed is reported in Table 8a. The mixed catalyst is prepared after gently shaking the particles together in a vial.

[0145] Table 8a shows the results of a process for converting synthesis gas to olefins under the following process conditions: H2 / CO is about 3; temperature is 420°C; pressure is equal to 40 bar (4,000 kPa); and GHSV is equal to 2400 / hour.

[0146] Table 8a

[0147]

[0148] Table 8a continued

[0149]

[0150] Example 6 demonstrates that Ga-ZrO2 can be produced using different preparation techniques; however, care must be taken to ensure that ZrO2 is delivered in a good crystalline form (e.g., monoclinic polymorph). The method used to obtain the very active component Ga-ZrO2 of the dual particle catalyst bed with SAPO-34 appears to be impregnation (Examples 1-5). However, under certain process operations, physical mixtures of ZrO2 and Ga2O3 may also acquire activity with extended process exposure, thereby affecting element redistribution in the presence of reactant and product gases.

[0151] It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the spirit and scope of the subject matter claimed for protection. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, provided that these modifications and variations fall within the scope of the appended claims and their equivalents.

Claims

1. A method for preparing C2 to C4 olefins, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; as well as The feed stream is converted into a product stream comprising C2 to C4 olefins in the reaction zone in the presence of a mixed catalyst comprising: A metal oxide catalyst component, the metal oxide catalyst component comprising gallium oxide and phase-pure zirconium oxide, wherein the phase-pure zirconium oxide comprises monoclinic phase-pure zirconium oxide or tetragonal phase-pure zirconium oxide, and wherein the BET surface area of ​​the phase-pure zirconium oxide is 30 m 2 / g to 150m 2 / g; and A microporous catalyst component comprising SAPO-34.

2. The method of claim 1, wherein the phase pure zirconia comprises crystalline phase pure zirconia.

3. The method according to claim 1 or 2, wherein the phase pure zirconia comprises monoclinic phase pure zirconia.

4. The method according to claim 1 or 2, wherein the BET surface area of ​​the phase-pure zirconium oxide is greater than or equal to 40 m 2 / g and less than or equal to 150m 2 / g.

5. The method according to claim 1 or 2, wherein the BET surface area of ​​the phase-pure zirconium oxide is greater than or equal to 100 m 2 / g and less than or equal to 150m 2 / g.

6. The process of claim 1 or 2, wherein the metal oxide catalyst component comprises greater than 0.0 g gallium per 100 g phase-pure zirconium oxide to 30.0 g gallium per 100 g phase-pure zirconium oxide.

7. The process of claim 1 or 2, wherein the metal oxide catalyst component comprises greater than 0.0 g of gallium per 100 g of phase-pure zirconium oxide to 15.0 g of gallium per 100 g of phase-pure zirconium oxide.

8. The method of claim 1 or 2, wherein the microporous catalyst component comprises an 8-membered ring structure.

9. The method according to claim 1 or 2, wherein the hybrid catalyst is prepared by physically mixing the metal oxide catalyst component and the microporous catalyst component.

10. The method according to claim 9, wherein the metal oxide catalyst component is calcined at a temperature of 500 to 600°C.

11. The method according to claim 1 or 2, wherein the metal oxide catalyst component accounts for 60.0 wt% to 90.0 wt% of the mixed catalyst.

12. The process of claim 1 or 2, wherein during the conversion, the temperature in the reaction zone is from 350°C to 450°C.

13. The process of claim 1 or 2, wherein during the converting, the pressure within the reaction zone is at least 1 bar (100 kPa).

14. The process of claim 1 or 2, wherein during the converting period, the GHSV within the reaction zone is from 1,200 / hour to 12,000 / hour.

15. The method according to claim 1 or 2, wherein the metal oxide catalyst component is formed by an impregnation method.

Citation Information

Patent Citations

  • Preparation of ethylene by use of synthetic gas

    CN1065026A